Preliminary results concerning the VSS X- chart with unknow in-control parameters - Castagliola, P.; Zhang, Y.; Costa, A. [UNESP]; Maravelakis, P. (Institute of Electrical and Electronics Engineers (IEEE), 2010)
The VSS X- chart is known to perform better than the traditional X- control chart in detecting small to moderate mean shifts in the process. Many researchers have used this chart in order to detect a process mean shift under the assumption of known parameters. However, in practice, the process parameters are rarely known and are usually estimated from an in-control Phase I data set. In this paper, we evaluate the (run length) performances of the VSS X- control chart when the process parameters are estimated and we compare them in the case where the process parameters are assumed known. We draw the conclusion that these performances are quite different when the shift and the number of samples used during the phase I are small. ©2010 IEEE.
Keywords: Estimated parameters; Run length; Variable sample size X- control chart; Control charts; Data sets; Estimated parameter; In-control; Mean shift; Number of samples; Phase I; Process mean shifts; Process parameters; Shift-and; Variable sample size; Flowcharting; Industrial engineering; Parameter estimation; Vector quantization; Process control